Valerie's home cooking : more than 100 delicious recipes to share with friends and family - Bertinelli, Valerie, 1960- (Oxmoor House, an imprint of Time Inc. Books, 2017)
Inspired by her family's cooking legacy, Bertinelli creates dishes that are for the heart and soul. Whether you're looking for a breakfast smoothie, tea sandwiches, or a lobster BLT, her recipes are fresh, vibrant, and down to search.